Impact of Module Degradation on the Viability of On-Grid Photovoltaic Systems in Mediterranean Climate: The Case of Shymkent Airport - Smagulov, Zhalgas; Anapiya, Adil; Dikhanbayeva, Dinara; Rojas-Solorzano, Luis (International Journal of Renewable Energy Development, 2021)
This paper presents the techno-economic feasibility analysis of an on-grid Photovoltaic Solar System (PVSS) subject to Mediterranean climate aging effects. The PVSS under study is considered installed on the roof of Shymkent airport, located in southern Kazakhstan. A PVSS performance degradation rate of 1.48%-per-annun was considered according to the Mediterranean climate prevailing in the location. A 25-year life-cycle cost analysis comparing the rated vs. de-rated on-grid PVSS led to a positive Net Present Value (NPV), a less than 9-year equity payback, and favorable internal rate of return (IRR) and Benefit-to-Cost (B-C) ratio in both conditions. However, the de-rated PVSS system underperformed in 16.2%, 43.5% and 20% the IRR, NPV and B-C ratio, respectively. The analysis demonstrates that despite the expected performance degradation associated to climatic aging, a convenient feed-in tariff (FIT) and attractive financial conditions, such as those present in Kazakhstan, conform a robust setting to promote on-grid PVSS in the country.